A Holomorphic Characterization of Operator Algebras - Neal, Matthew; Russo, Bernard (Mathematica Scandinavica, 2014)
A necessary and sufficient condition for an operator space to support a multiplication making it completely isometric and isomorphic to a unital operator algebra is proved. The condition involves only the holomorphic structure of the Banach spaces underlying the operator space.